Penjaminan Hak Atas Tanah oleh Penjual yang Objeknya Telah Terikat dalam Perjanjian - Qalby Rahman, Tenriana Nur (UNES Law Review, 2023)
The Binding Purchase Agreement (PPJB) occurs when there are conditions of land purchase that have not been fulfilled yet. PPJB provides an opportunity for sellers with ill intentions to sell or pledge their land to a third party outside of PPJB. This is due to the fact that the certificate is still in the seller's name and there is no information available about the land being bound in PPJB. This study addresses two main issues, namely the position of the encumbrance rights on the land that has been sold based on PPJB, and secondly, the legal protection for the buyer in PPJB and the creditor as the party with good intentions. The research method used is doctrinal legal research conducted through document study. The type of research used is explanatory. The results of this research indicate that the imposition of rights over the land by the creditor as the seller in the Binding Purchase Agreement (PPJB), which has been fully paid, can be canceled due to good intentions. Legal protection is provided by stating that the buyer with good intentions is the rightful owner of the disputed land, while for the creditor, the protection given is not to cancel the Encumbrance Rights, but to renew the object of Encumbrance Rights on other assets owned by the debtor.